2008
DOI: 10.1093/aje/kwn096
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in Adolescence in Relation to Cause-specific Mortality: A Follow-up of 230,000 Norwegian Adolescents

Abstract: The prevalence of obesity in childhood and adolescence has increased worldwide. Long-term effects of adolescent obesity on cause-specific mortality are not well specified. The authors studied 227,000 adolescents (aged 14-19 years) measured (height and weight) in Norwegian health surveys in 1963-1975. During follow-up (8 million person-years), 9,650 deaths were observed. Cox proportional hazards regression was used to compare cause-specific mortality among individuals whose baseline body mass index (BMI) was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
256
4
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(283 citation statements)
references
References 27 publications
11
256
4
8
Order By: Relevance
“…Of course, there is always the possibility of residual confounding (especially due to the self-reported nature of many of the variables considered), as well as the potential contribution of variables not considered here, such general health status. Indeed, the U-shaped pattern in the association between adiposity and vitamin D status as described in our study mirrors the pattern observed between BMI or BF% and mortality or morbidity for a number of diseases in all age groups, including adolescents (43)(44)(45) . Baumgartner et al in their review report the lack of studies on the relationship of low BMI and BF% with morbidity and mortality (45) and comment on the fact that reported associations between underweight and chronic diseases often do not have a plausible physiological explanation.…”
Section: Predictors Of Vitamin D Levels and Statussupporting
confidence: 85%
“…Of course, there is always the possibility of residual confounding (especially due to the self-reported nature of many of the variables considered), as well as the potential contribution of variables not considered here, such general health status. Indeed, the U-shaped pattern in the association between adiposity and vitamin D status as described in our study mirrors the pattern observed between BMI or BF% and mortality or morbidity for a number of diseases in all age groups, including adolescents (43)(44)(45) . Baumgartner et al in their review report the lack of studies on the relationship of low BMI and BF% with morbidity and mortality (45) and comment on the fact that reported associations between underweight and chronic diseases often do not have a plausible physiological explanation.…”
Section: Predictors Of Vitamin D Levels and Statussupporting
confidence: 85%
“…1,2 Unfortunately, the prevalence of adolescent obesity has more than tripled over the past 4 decades (5.2% to 18.4%). 3,4 The rise in obesity has been paralleled by decreases in the amount of time that adolescents have spent sleeping, 5 leading to the hypothesis that short sleep duration has contributed to the rise in adolescent obesity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Obesity in childhood is strongly associated with increased incidence of premature death. 2,3 As of 2008, the World Health Organization estimated that B1.5 billion adults were overweight and at least 500 million adults were obese. The worldwide prevalence of childhood overweight and obesity had attained 6.7% by 2010.…”
Section: Introductionmentioning
confidence: 99%